Diamanti, magneti e altre noterelle di mineralogia nella lirica medievale (Carte Romanze, 2020)
The essay proposes a sampling of mineralogical images in medieval Romance lyric: we will focus, in particular, on the image of the diamond. At least in some cases, it seems legitimate to suppose the mediation of a literary source; for some, on the other hand, it is possible to read a refunctionalization within the ideology of fin’amor.
Keywords: medieval Romance lyric; lapidaries; diamond.